2013
DOI: 10.1186/1471-2377-13-164
|View full text |Cite
|
Sign up to set email alerts
|

Visual pursuit response in the severe disorder of consciousness: modulation by the central autonomic system and a predictive model

Abstract: BackgroundA visual pursuit response is reportedly observed in ~20-30% of subjects in vegetative state (VS/UWS) and predicts better outcome; it is a key marker of evolution into the minimally conscious state (MCS). The probability of observing a positive response, however, has proven variable during the day, with comparable timing of the minima and maxima in VS/UWS and MCS. We verified if measures of sympathetic/parasympathetic balance are possible independent variables on which the occurrence of a pursuit resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…There were no other differences on a range of factors studied, including prognosis 23. In another study, 5 of 14 patients in the vegetative state showed visual pursuit, as compared with 12 of 16 patients in a minimally conscious state 24. In a third study of variability in performance, which found that responsiveness was best in the morning, it was found that three of nine people in the vegetative state showed visual pursuit on at least one occasion, and conversely that 5 of 13 people in a minimally conscious state did not 25…”
Section: Visual Fixation and Pursuitmentioning
confidence: 89%
“…There were no other differences on a range of factors studied, including prognosis 23. In another study, 5 of 14 patients in the vegetative state showed visual pursuit, as compared with 12 of 16 patients in a minimally conscious state 24. In a third study of variability in performance, which found that responsiveness was best in the morning, it was found that three of nine people in the vegetative state showed visual pursuit on at least one occasion, and conversely that 5 of 13 people in a minimally conscious state did not 25…”
Section: Visual Fixation and Pursuitmentioning
confidence: 89%
“…For example, one could compare common programs of environmental stimulation with learning-based intervention programs on measures such as attention and alertness. To this end, one could gather data on eye-opening time, orienting, and head movements or on heart-rate variability under the different conditions Lancioni et al 2014c;Riganello et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The visual pursuit response is a major CRS-r item observed in 70–80% of subjects in MCS [ 34 36 ] and a key marker of evolution from VS/UWS [ 37 , 38 ]; it has been reported with lower incidence (~20–30%) also in subjects otherwise unambiguously diagnosed as VS/UWS [ 10 , 29 , 39 , 40 ]. The controversy on whether this or other responses may indicate residual automatic subcortical activities compatible with, but atypical for, VS/UWS or may rather signal higher order cortical activation and partially recovered consciousness remains unsolved [ 20 ].…”
Section: Responsiveness and Individual Variabilitymentioning
confidence: 99%